2018
DOI: 10.1038/s41594-018-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus infection causes global RNAPII termination defects

Abstract: Viral infection perturbs host cells and can be used to uncover regulatory mechanisms controlling cellular responses and susceptibility to infections. Using cell biological, biochemical, and genetic tools, we reveal that influenza A virus (IAV) infection induces global transcriptional defects at the 3' ends of active host genes and RNA polymerase II (RNAPII) run-through into extragenic regions. Deregulated RNAPII leads to expression of aberrant RNAs (3' extensions and host-gene fusions) that ultimately cause gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 100 publications
6
63
3
Order By: Relevance
“…There is evidence in the literature that IAV infection results in reduced host transcription and mRNA processing by inhibiting the host RNA polymerase II (Pol II) function (60,61). Related to this, a recent study found that several strains of IAV elicit global deregulation of Poll II transcription termination by impairing 3=-end cleavage and termination, and this effect was dependent on NS1 expression (62). These studies could partially explain the global negative correlation that we found between viral genes and cellular genes.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in the literature that IAV infection results in reduced host transcription and mRNA processing by inhibiting the host RNA polymerase II (Pol II) function (60,61). Related to this, a recent study found that several strains of IAV elicit global deregulation of Poll II transcription termination by impairing 3=-end cleavage and termination, and this effect was dependent on NS1 expression (62). These studies could partially explain the global negative correlation that we found between viral genes and cellular genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that transcription termination is regulated by viral infections and cellular stresses [13][14][15]40 , and that increased DoTT is associated with cancer 16 . To understand the underlying mechanisms, we carried out an in-depth study of HSV-1-induced DoTT.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA 3′ processing factors are also targeted by other viruses. For example, influenza virus infection or ectopic expression of the influenza viral protein NS1 causes transcription termination defects of host genes 40,41 . NS1 inhibits host mRNA 3′ processing by specifically binding to the CPSF subunit CPSF30 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies observing altered genome architecture, transcript 3’ end defects, and PA-X targeted transcript degradation during infection all have links to splicing (Gaucherand et al, 2019; Heinz et al, 2018; Zhao et al, 2018). One observation was that of transgenic, defective, and unannotated splicing in relation to transcription termination (Heinz et al, 2018; Zhao et al, 2018). While our splicing analyses did not account for these specific splicing types, we would predict for them to be present in our experiments to some extent.…”
Section: Discussionmentioning
confidence: 99%